Konflik Antar Etnis di Indonesia dalam Analisis Face Negotiation Theory - Muhammad Rachdian Al Azis; Irwansyah Irwansyah (Faculty of Social Science, Universitas Negeri Padang, 2021)
Indonesia is known as a country with a pluralistic society. With the wealth of ethnicity, ethnicity, race, and religion in it, this multicultural society then becomes prone to friction. Not to mention the differences in terms of language, customs, and habits in it. These frictions will in turn lead to conflicts which are then unavoidable. The study of inter-ethnic conflict in Indonesia in the analysis of face negotiation theory was carried out with several objectives, which are: to explain the analysis of face negotiation theory in several cases of ethnic conflict that occurred in Indonesia so that it is expected to be taken into consideration in preventing or dealing with similar conflicts. The method used in this research is qualitative with data sources obtained through literature study (Creswell, 2012). The result of the research is that in the Indonesian phenomenon, many sources said that usually the way Indonesian people in determining their attitude during conflict are by integration or mutual - face. Where the characteristics in it are Apologize, Private talk, Remain calm, Problem solve, and Respect. This behavior is a characteristic of collectivistic culture that is indeed embraced by Indonesian people in general